Patriarchal Ideology And Women's Resistance In “Women Talking” Film (2022): A Semiotic Analysis Of Roland Barthes - Serilova, Siska; Fitriyah (Universitas Cokroaminoto Palopo, 2026)
Semiotics is the study of signs and how meanings are constructed through denotation, connotation, and myth. The research aims to analyze the patriarchal ideology and women's resistance in “Women Talking” (2022) by Sarah Polley. The film depicts the tragic experiences of women in a closed religious’ colony who are victims of systematic sexual violence, as well as facing social pressures and religious doctrine that demands that they forgive the perpetrators. Using qualitative descriptive methods and Roland Barthes' semiotic approach, this study examines the meanings embedded in symbols, dialogues, and scenes that represent the collective consciousness, solidarity, and women's struggle against the patriarchal system. The data analysis consists of four stages: watching the film, identifying the dialogue or scenes into denotative, connotative, and myth, then analysing, and finally drawing a conclusion. As a result, there are ten dialogues and scenes that were analyzed using Barthes’ semiotics. In conclusion, this film showed how meaning operates on denotative, connotative, and mythical levels to expose and resist patriarchal ideology.